2013
DOI: 10.1016/j.jvs.2013.05.027
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of patients on hemodialysis with foot lesions

Abstract: Hemodialysis patients with foot lesions have a poor prognosis, with high rates of mortality and amputation. Prompt assessments of the severity of systemic conditions, such as cardiac ischemia, and focal wound conditions, such as ischemia and infection, are necessary to treat hemodialysis patients with foot lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…These results remain within previous literature reported ranges at similar time points (AFS, 15%–23% 2,25,26 and survival, 20%–50% 1,2,4,7,28,29 ) and highlight a lack of temporal improvement in treatment of HD patients with critical limb ischemia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results remain within previous literature reported ranges at similar time points (AFS, 15%–23% 2,25,26 and survival, 20%–50% 1,2,4,7,28,29 ) and highlight a lack of temporal improvement in treatment of HD patients with critical limb ischemia.…”
Section: Discussionsupporting
confidence: 90%
“…16 With less than 25% of HD patients with a foot lesion alive at 5 years, the prognosis of a HD patient with peripheral artery disease (PAD) remains worse than most cancers. 7 Furthermore, PAD is a common and growing problem in HD patients. PAD has been shown to affect nearly one-third of patients on HD, 8 and, according to the U.S. Department of Health and Human Services, end-stage renal disease (ESRD) has increased by 600% over the past three decades.…”
mentioning
confidence: 99%
“…In other studies, hyperlipidaemia has been reported in 5e23% of patients. 13,16,26 Other reports have shown that myocardial infarction, congestive heart failure, and CAD are predictors of survival. 27,28 The present study showed that non-ambulatory status was one of the negative predictors of limb salvage, AFS, and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as diabetic patients with end-stage renal disease (ESRD) resulting from diabetic nephropathy are increasing annually, HD patients are also increasing. 1 According to the Japanese Society for Dialysis Therapy Annual Report, the total HD population surpassed 300,000 at the end of 2011, with HD patients making up a high proportion of the total population at 0.24%. 2 Peripheral artery disease (PAD) is common among HD patients, and in HD patients it is often detected with the onset of critical limb ischemia (CLI) with recalcitrant ulcers or gangrene.…”
Section: Introductionmentioning
confidence: 99%